2022
DOI: 10.5194/bg-19-1451-2022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the South-East Madagascar Bloom on the oceanic CO<sub>2</sub> sink

Abstract: Abstract. We described new sea surface CO2 observations in the south-western Indian Ocean obtained in January 2020 when a strong bloom event occurred south-east of Madagascar and extended eastward in the oligotrophic Indian Ocean subtropical domain. Compared to previous years (1991–2019) we observed very low fCO2 and dissolved inorganic carbon concentrations (CT) in austral summer 2020, indicative of a biologically driven process. In the bloom, the anomaly of fCO2 and CT reached respectively −33 µatm and −42 µ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Our conclusion that N 2 fixation occurs locally in the greater Agulhas region is consistent with previous observations. First, diazotrophs have been observed during the late‐summer bloom that occurs irregularly to the southeast of Madagascar (Poulton et al., 2009), as well as within and south of the Mozambique Channel (Huggett & Kyewalyanga, 2017; Karlusich et al., 2021), with surface N 2 fixation rates of 2–18 nM.d −1 measured southeast of Madagascar during the most recent (2020) late‐summer bloom (Metzl et al., 2022). Second, one third of the thermocline nitrate at the north‐eastern edge of the greater Agulhas region (∼23°S, 70°E; Figure 1) has previously been estimated to be newly fixed based on subsurface nutrient N:P ratios (Harms et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our conclusion that N 2 fixation occurs locally in the greater Agulhas region is consistent with previous observations. First, diazotrophs have been observed during the late‐summer bloom that occurs irregularly to the southeast of Madagascar (Poulton et al., 2009), as well as within and south of the Mozambique Channel (Huggett & Kyewalyanga, 2017; Karlusich et al., 2021), with surface N 2 fixation rates of 2–18 nM.d −1 measured southeast of Madagascar during the most recent (2020) late‐summer bloom (Metzl et al., 2022). Second, one third of the thermocline nitrate at the north‐eastern edge of the greater Agulhas region (∼23°S, 70°E; Figure 1) has previously been estimated to be newly fixed based on subsurface nutrient N:P ratios (Harms et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, N 2 fixation must be significant elsewhere in the Indian Ocean (Deutsch et al, 2007;Grand, Measures, Hatta, Morton, et al, 2015;Gruber & Sarmiento, 1997;Wang et al, 2019), yet there are almost no observations of this process, particularly from the southern basin (cf. Harms et al, 2019;Karlusich et al, 2021;Metzl et al, 2022;Poulton et al, 2009).…”
mentioning
confidence: 99%
“…However, this would not dramatically impact the mean CO 2 fluxes assuming that over 1985-2018 ocean pCO 2 increase is close to the atmospheric growth rate as observed in some parts of the Indian Ocean (e.g. Metzl, 2009;Lauvset et al, 2015;Metzl et al, 2022;Lo Monaco et al, 2021).…”
Section: Observational Climatologymentioning
confidence: 97%
“…Despite the importance of the Indian Ocean in the global carbon cycle, this region is poorly studied with reference to the biogeochemical cycling of carbon compared to the other two major basins. The seasonal cycle of pCO 2 and carbon fluxes was studied only in the Arabian Sea (Chakraborty et al, 2021;De Verneil et al, 2022;George et al, 1994;Goyet et al, 1998;Sarma et al, 1998Sarma et al, , 2003Sarma et al, , 2013, the BoB (Chakraborty et al, 2021;Sarma et al, 2012Sarma et al, , 2015Sarma et al, , 2020Sarma, Krishna, et al, 2021) and the south-western Indian ocean (Metzl et al, 1998) whereas the long-term variability was only recently studied in the southwestern Indian Ocean region (Metzl et al, 2022) as the other regions in the Indian Ocean was either sampled once or twice during last few decades (Sarma et al, 2013;Takahashi et al, 2009). The studies carried out in the aegis of the Joint Global Flux Study (JGOFS) and the Bay of Bengal Process Studies (BoBPS) suggested that the seasonal amplitude of pCO 2 goes beyond 200 μatm in the Arabian Sea (George et al, 1994;Goyet et al, 1998;Sarma et al, 1998Sarma et al, , 2003 and BoB (Kumar et al, 1996;Sarma et al, 2012Sarma et al, , 2015Sarma et al, , 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation